Discrete Second-Order Sliding Mode Adaptive Controller Based on Characteristic Model for Servo Systems - Zhihong Wang; Yifei Wu; Wei Chen; Xiang Wang; Jian Guo; Qingwei Chen (Journal of Control Science and Engineering)
Considering the varying inertia and load torque in high speed and high accuracy servo systems, a novel discrete second-order sliding mode adaptive controller (DSSMAC) based on characteristic model is proposed, and a command observer is also designed. Firstly, the discrete characteristic model of servo systems is established. Secondly, the recursive least square algorithm is adopted to identify time-varying parameters in characteristic model, and the observer is applied to predict the command value of next sample time. Furthermore, the stability of the closed-loop system and the convergence of the observer are analyzed. The experimental results show that the proposed method not only can adapt to varying inertia and load torque, but also has good disturbance rejection ability and robustness to uncertainties.